A pilot randomized clinical trial of γ-tocopherol supplementation on wood smoke–induced neutrophilic and eosinophilic airway inflammation - David B. Peden, MD; Martha Almond, RRT; Christian Brooks, BS; Carole Robinette, MS; Heather Wells, MS; Allison Burbank, MD; Michelle Hernandez, MD; Alan Hinderliter, MD; Melissa Caughey, PhD; Qing Jiang, PhD; Qianyue Wang, MS; Haolin Li, BSPH; et al. (Journal of Allergy and Clinical Immunology: Global, 2023)
Background: Air pollutants, including particulates from wood smoke, are a significant cause of exacerbation of lung disease. γ-Tocopherol is an anti-inflammatory isoform of vitamin E that has been shown to reduce allergen-, ozone-, and endotoxin-induced inflammation. Objective: The objective of this study was to determine whether γ-tocopherol would prevent experimental wood smoke–induced airway inflammation in humans. Methods: This was a randomized, placebo-controlled clinical trial testing the effect of a short course of γ-tocopherol–enriched supplementation on airway inflammation following a controlled exposure to wood smoke particulates. Results: Short-course γ-tocopherol intervention did not reduce wood smoke–induced neutrophilic airway inflammation, but it did prevent wood smoke–induced eosinophilic airway inflammation. Conclusion: γ-Tocopherol is a potential intervention for exacerbation of allergic airway inflammation, but further study examining longer dosing periods is required.